Financial fragility and the exchange rate regime - Roberto Chang; Andres Velasco (Federal Reserve Bank of Atlanta, 1997)
We study financial fragility, exchange rate crises, and monetary policy in an open economy version of a Diamond-Dybvig model. The banking system, the exchange rate regime, and central bank credit policy are seen as parts of a mechanism intended to maximize social welfare; if the mechanism fails, banking crises and speculative attacks become possible. We compare currency boards, fixed rates, and flexible rates with and without a lender of last resort. A currency board cannot implement a socially optimal allocation; in addition, bank runs are possible under a currency board. A fixed exchange rate system may implement the social optimum but is more prone to bank runs and exchange rate crises than a currency board. A flexible rate system implements the social optimum and eliminates runs, provided the exchange rate and central bank lending policies are appropriately designed.
Keywords: 330; Banks and banking; Central; Financial crises; Financial institutions; Foreign exchange rates